Formulation of a poly herbal gel for uterus flux - M. Rezghi; S. Zakerin; H. Hajimehdipoor*; M. Hamzeloo-Moghadam (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Over the centuries, herbal drugs have been used as major sources of medicine for the prevention and treatment of diseases. In recent years, there has been an exponential growth in the field of herbal medicines and these drugs are gaining popularity both in developing and developed countries because of their natural origin and less side effects. The present research has been undertaken to formulate and evaluate an herbal gel for uterus flux based on Iranian traditional medicine references. Methods: An aqueous extracts of fruit peels of Punica granatum and leaves of Myrtus communis, ethanol extract of oleo gum resins of Boswellia carterii and hydro-alcoholic extract of Carum carvi fruits were obtained. The gel was prepared by using the plants extract, carbopol 940, propylene glycol, tri-ethanolamine and distilled water. Further, the prepared gel was evaluated for physicochemical and microbial characteristics. Moreover, accelerated laboratory stability tests were performed. Results: The results showed good appearance and homogeneity of the gel. It was yellow-brown in color with acceptable physicochemical characteristics. Besides, the gel was stable towards physical changes and successfully passed microbiological tests. Conclusion: The prepared gel contained tannins which are astringent agents; therefore, this product could be an appropriate candidate for disorders like uterus flux with respect to its traditional use.